2000
DOI: 10.1136/gut.46.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Long term efficacy, safety, and tolerabilitity of low daily doses of isosmotic polyethylene glycol electrolyte balanced solution (PMF-100) in the treatment of functional chronic constipation

Abstract: Aims-To assess the long term therapeutic eVectiveness, safety, and tolerability of low daily doses of isosmotic PEG electrolyte solutions (PMF-100) administered for a six month period for the treatment of functional constipation, in a double blind, placebo controlled, parallel group study. Methods-After an initial four week run in period with PMF-100 (250 ml twice daily; PEG 14.6 g twice daily), 70 patients suVering from chronic constipation (58 females, aged 42 (15) years) with normalised bowel frequency (>3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 9 publications
(7 reference statements)
8
90
1
7
Order By: Relevance
“…19 In fact, some studies also reported efficacy at a low dosage of PEG. [145][146][147] For lactulose, at least 2 systematic reviews reported RCTs showing efficacy over placebo, 109,110 and the evidence is considered superior. No randomized, placebo-controlled trials have been conducted with sorbitol, but at least 1 double-blind, randomized, crossover study showed no difference in efficacy when compared with lactulose.…”
Section: Osmotic Agentsmentioning
confidence: 99%
“…19 In fact, some studies also reported efficacy at a low dosage of PEG. [145][146][147] For lactulose, at least 2 systematic reviews reported RCTs showing efficacy over placebo, 109,110 and the evidence is considered superior. No randomized, placebo-controlled trials have been conducted with sorbitol, but at least 1 double-blind, randomized, crossover study showed no difference in efficacy when compared with lactulose.…”
Section: Osmotic Agentsmentioning
confidence: 99%
“…119 While osmotic laxatives can generally cause electrolyte disturbances, volume overload, or dehydration, and these medications should be used with caution in patients prone to renal insufficiency or cardiac abnormalities, 131 PEG is considered relatively safe in these respects. Although there have been reports about common adverse events including diarrhea, ab-dominal pain, nausea, and vomiting, no serious adverse events have been reported with long-term PEG treatment.…”
mentioning
confidence: 99%
“…Numerous trials have shown both electrolyte-enriched PEG and electrolyte-free PEG to be effective in patients with chronic constipation. 115,[118][119][120][121][122][123][124][125][126][127] A meta-analysis concluded that PEG treatment resulted in a highly significant increase in defecations per week over placebo. 128 In particular, a meta-analysis involving 10 RCTs found that PEG was better than lactulose with respect to the outcomes of stool frequency per week, form of stool, relief of abdominal pain, and the need for additional products.…”
mentioning
confidence: 99%
“…Большинство экспертов по запорам предлагают несколько вариантов лечения хронического запора с первоначальными реко-мендациями по изменению образа жизни, а при неудаче этого подхода предлагают использовать осмотические, увеличивающие объем каловых масс и стимулирующие слабительные. Использование макрогола, бисакодила, гли-цериновых суппозиториев, фосфата натрия и клизмы с арахисовым маслом также является обычной практикой перед использованием относительно инновационных агентов [5][6][7][8][9][10][11][12][13][14][15]. В различных источниках с переменной эффективностью обсуждаются нефармакологические вме-шательства, такие как ритуализирующие привычки для кишечника, терапия биологической обратной связи, пове-денческая терапия, электростимуляция мышц таза, когни-тивная терапия и хирургические пособия на толстой кишке у пациентов с хроническим запором [16][17][18][19].…”
unclassified